2018
DOI: 10.1111/iej.12889
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility of Biodentine and iRoot FS with human periodontal ligament cells: an in vitro study

Abstract: iRoot FS had a positive effect on the adhesion, proliferation and biomineralization of hPDLCs compared with Biodentine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
4
16
0
Order By: Relevance
“…Moreover, hSCAP cultured in iRoot FS conditioned medium had significantly greater expression levels of ALP and DSPP, and more formation of mineralized nodules than the MTA group. Those data demonstrated that iRoot FS was superior in facilitating osteo/odontogenic differentiation of hSCAP, consistent with previous studies (Peng et al , Sun et al , Luo et al ). However, the detailed molecular mechanism of how iRoot FS promotes osteo/odontogenic differentiation is not reported.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, hSCAP cultured in iRoot FS conditioned medium had significantly greater expression levels of ALP and DSPP, and more formation of mineralized nodules than the MTA group. Those data demonstrated that iRoot FS was superior in facilitating osteo/odontogenic differentiation of hSCAP, consistent with previous studies (Peng et al , Sun et al , Luo et al ). However, the detailed molecular mechanism of how iRoot FS promotes osteo/odontogenic differentiation is not reported.…”
Section: Discussionsupporting
confidence: 91%
“…Both iRoot FS and MTA are calcium phosphate silicate cement (CPSC) (Lu & Zhou ). Several studies have indicated that CPSC materials have the potential to boost osteo/odontogenic differentiation by increasing the expression of osteo/odontogenic markers and calcium deposit (Peng et al , Sun et al , Luo et al ). In the present study, the osteo/odontogenic differentiation of hSCAP exposed to both iRoot FS and MTA was enhanced markedly compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, both the cellular processes (migration and adhesion) play a key role in the maintenance of tissue homeostasis, repair and regeneration. Therefore, to make these goals achievable, cells must be able to migrate and adhere to the targeted sites for regeneration and development of functional tissues [33,39]. As previously described [40], dental stem cells respond to these injuries by these cellular processes; proliferation, differentiation, migration and adhesion in order to repair and replace the damaged tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Biodentine™ (BD) is relatively a new calcium silicate-based cement, synthesized to be used in direct contact with the periodontal ligament, which is crucial in conservative therapy. It has been suggested that the attachment of cells to the root surface is a critical and complicated dynamic process, which has implications in biological processes, such as cell proliferation and differentiation [33]. The effect of Biodentine™ on the adhesive ability of fibroblasts of PDL has been reported (40).…”
Section: Discussionmentioning
confidence: 99%